2018
DOI: 10.2147/cia.s171307
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the vitamin D metabolism in the development of periprosthetic infections after THA and TKA: a prospective matched-pair analysis of 240 patients

Abstract: BackgroundThe importance of the vitamin D homeostasis in infections is already known. However, its significance in periprosthetic infections (PPIs) after total hip arthroplasty and total knee arthroplasty is largely unexplored. The aim of the study is to precisely analyze the vitamin D balance in patients with PPIs after total hip arthroplasty and total knee arthroplasty. Here, cases with primary endoprosthesis implants and aseptic loosening are used as comparison groups.Materials and methodsIn this prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…Five studies were of high methodological quality, 11 , 14 , 15 , 18 , 21 12 were of moderate quality 12 , 13 , 16 , 17 , 19 , 20 , 22 - 25 , 27 , 28 and 1 of low quality. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were of high methodological quality, 11 , 14 , 15 , 18 , 21 12 were of moderate quality 12 , 13 , 16 , 17 , 19 , 20 , 22 - 25 , 27 , 28 and 1 of low quality. 26 …”
Section: Resultsmentioning
confidence: 99%
“… 29 , 30 Several studies have reported a correlation between vitamin D levels and functional status as well as the risk of complications following TJA with conflicting outcomes. 11 – 14 , 16 However, the literature is still inconsistent in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…На підставі аналізу метаболічних показників у 240 хворих із перипротезною інфекцією після первинного та ревізійного ендопротезування колінного та кульшового суглобів встановлено зниження рівня вітаміну D, кальцію, альбуміну та загального білка [43]. Рекомендовано призначати вітамін D разом із кальцієм та одночасною корекцією білкового балансу.…”
Section: поширеність дефіциту та недостатності вітаміну D у хворих доunclassified
“…Визначено, що вітамін D має виражену дію на штами Staphylococcus aureus, Streptococcus pyogenes, Klebsiella pneumoniae, Escherichia coli та інші бактерії. За його присутності в культуральному середовищі вказані мікроорганізми гинули або було виявлено значне пригнічення їхнього росту [43].…”
Section: поширеність дефіциту та недостатності вітаміну D у хворих доunclassified
“…Уровень сывороточного 25OHD был сопоставим во всех группах, тогда как в обеих группах контроля наблюдалось значительное повышение уровня кальция и щелочной фосфатазы и снижение уровня белкового баланса. При острых инфекционных осложнениях наблюдалось и снижение уровня сывороточного 25OHD [7]. Signori V. и соавт.…”
unclassified